Micro Jumps, Macro Humps: Monetary Policy and Business Cycles in an Estimated HANK Model - Adrien Auclert; Matthew Rognlie; Ludwig Straub (Center for Economic Studies and ifo Institute (CESifo), 2020)
We estimate a Heterogeneous-Agent New Keynesian model with sticky household expectations that matches existing microeconomic evidence on marginal propensities to consume and macroeconomic evidence on the impulse response to a monetary policy shock. Our estimated model uncovers a central role for investment in the transmission mechanism of monetary policy, as high MPCs amplify the investment response in the data. This force also generates a procyclical response of consumption to investment shocks, leading our model to infer a central role for these shocks as a source of business cycles.
Keywords: E21; E22; E32; E43; E52; E70; 330; HANK; estimation; investment